A Dynamic Narrative Communication System in Indonesian B2B Manufacturing: Constructing Identity, Legitimacy, and Strategic Integration - Asih HandayantI; Erik Hadi Saputra (INJECT (Interdisciplinary Journal of Communication), 2026)
In the contemporary digital communication landscape, manufacturing organizations face mounting pressure to move beyond episodic messaging toward sustained, systems-level narrative frameworks. This study investigates how strategic storytelling functions as the operational core of a Dynamic Narrative Communication System (DNCS) within the Marketing Public Relations (MPR) activities of a business-to-business (B2B) manufacturing company in Indonesia. The research employed a qualitative case study methodology, collecting data through in-depth interviews with key communication practitioners, systematic analysis of digital documents, and multi-platform observational studies across corporate websites, social media channels, and regulatory submission materials. Findings demonstrate that storytelling in this context operates across three interconnected dimensions: organizational identity construction, social legitimacy acquisition in relation to government regulatory compliance, particularly Indonesia's green industry standards and domestic component requirements,and strategic communication integration. The DNCS model proposed herein conceptualizes narrative not as a discrete tactical instrument but as a dynamic systemic mechanism through which manufacturing firms maintain reputational stability and adaptive capacity amid shifting government policies and evolving digital environments. This research contributes a theoretically grounded, empirically validated framework that extends storytelling scholarship into the underexplored domain of B2B manufacturing communication and government-industry relations.